Studi Sistem Tumpangsari Budidaya Jagung Manis (Zea mays Saccharata) Varietas Bonanza dan Lima Aksesi Kacang Bambara (Vigna subterranea) - Al Hamdi, Muhammad Fauzan Farid; Hidayat, Fajar (Journal TECHNO, 2024)
Sweet corn (Zea mays Saccharata Strut) and bambara groundnut (Vigna subterranea (L.) Verdc) are very likely to be intercropped, because bambara groundnut are legumes that function to fix nitrogen from the free air which is beneficial for sweet corn plants. This study aimed to determine the growth and productivity responses of corn plants and 5 accessions of bambara beans in an intercropping system. The study was conducted in Sariharjo village, Ngaglik, Sleman, in July-October 2024. The experimental design used was a split-plot Randomized Block Design (RBD) with two factors with 3 replications. The main factor is the number of corn seeds per hole with 2 levels (1 seed per hole and 2 seeds per hole), and the sub factor is the type of bambara groundnut accession. The sub-factors consisted of 6 levels, namely the intercropping system of corn and 5 accessions of bambara groundnut: Bogor, Sukabumi, Sumedang brown, Madura and Gresik accessions and monoculture of corn plants, so that there were 36 experimental units. The results of this study concluded that the intercropping cultivation system of sweet corn with bambara groundnut significantly increased plant height, while the intercropping of sweet corn and bambara groundnut of Madura and Gresik accessions significantly increased the weight of sweet corn cobs. In all variables, Madura and Gresik accessions showed no significant differences. Sweet corn with 2 plants per planting hole is less efficient in producing corn cobs and has a negative impact on number of leaves and flowering age  of bambara groundnut.